A computational tool for estimating stress fields along a surface crack front. Issue 2 (19th May 2014) - Chernyatin, A. S.; Matvienko, Y. G.; Razumovsky, I. A.; James, M. N; Susmel, L.; Iacoviello, F.; Hong, Y.; Patterson, E. A.; Lopez‐Crespo, P.
Abstract A combined experimental and computational method for determination of the singular and non‐singular stress terms along the front of the 3D surface crack is proposed. It is suggested to evaluate the terms by means of comprehensive comparison between deformation responses on the structure surface in the vicinity of the crack obtained experimentally and from numerical solutions of the corresponding boundary problem of solid mechanics. As the deformation response, a local displacement field caused by the formation of a small hole at the tip of the crack recorded by digital speckle pattern interferometry may be considered. The proposed approach allows defining such real parameters of the structure as the active load conditions in the crack region and crack sizes. These parameters are used to solve the direct problem and to determine the stress intensity factor KI and Txx‐, Tzz‐stresses along the surface crack front by means of an improved technique of their calculation. The approach accuracy and stability at different conditions have been proved by means of numerical simulation that examined half‐space with planar semi‐elliptical surface crack under biaxial loading. So, the potential applicability of the proposed method is demonstrated. The biaxiality effect on KI and Txx, Tzz is discussed.